Sustainability analysis of rapid prototyping: material/resource and process perspectives. (1st January 2013) - Ullah, A.M.M. Sharif; Hashimoto, Hiroyuki; Kubo, Akihiko; Tamaki, Jun'ichi
Sustainability of rapid prototyping (RP) depends on both model-building materials (wooden-materials, photo-resins, etc.) and model-building processes (additive processes – SLA, SLS, etc.; and subtractive processes – e.g., wood-sawing). In this study, a sustainability index is developed for RP processes, and this index incorporates such sustainability factors as volumetric quantity of model-building material, CO2 footprint and resource depletion of primary production of model-building material, energy consumption and CO2 emission of the model-building process. In addition, physical models have been created from the same 3D CAD data by using both SLA-based RP technology (additive process) and wooden-material-based RP technology (subtractive process). The subtractive process uses a specially designed CNC machine tool that removes the wooden-material using a circular-saw controlled by a 3D CAD model. The model-building process has been repeated for different scales of the same 3D CAD model. Using the experimental results, the sustainability index of the two RP technologies has been compared. The results help determine the critical size of a physical model of a given 3D CAD model and RP technology ensuring sustainability. In addition, the results show new avenues for improving the respective RP technologies in terms of sustainable manufacturing requirements.